2020
DOI: 10.1111/brv.12639
|View full text |Cite
|
Sign up to set email alerts
|

Rate of environmental change across scales in ecology

Abstract: The rate of change (RoC) of environmental drivers matters: biotic and abiotic components respond differently when faced with a fast or slow change in their environment. This phenomenon occurs across spatial scales and thus levels of ecological organization. We investigated the RoC of environmental drivers in the ecological literature and examined publication trends across ecological levels, including prevalent types of evidence and drivers. Research interest in environmental driver RoC has increased over time … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 155 publications
1
43
0
Order By: Relevance
“…For instance, a recent study, using a model whose parameters were estimated from data, showed that behavioural feedbacks may cause rate-induced regime shifts in coral reefs [31]. However, determining whether a regime shift observed in the past was caused by the rate of change of an environmental condition may be challenging due to the lack of data on the effects of the rate of change in ecosystems [39]. Furthermore, documented regime shifts at the ecosystem scale rarely include information about trait changes of the organisms involved [10], which is necessary to study the feedbacks between ecological and evolutionary processes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study, using a model whose parameters were estimated from data, showed that behavioural feedbacks may cause rate-induced regime shifts in coral reefs [31]. However, determining whether a regime shift observed in the past was caused by the rate of change of an environmental condition may be challenging due to the lack of data on the effects of the rate of change in ecosystems [39]. Furthermore, documented regime shifts at the ecosystem scale rarely include information about trait changes of the organisms involved [10], which is necessary to study the feedbacks between ecological and evolutionary processes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent patterns in RoC peaks in several sequences may potentially indicate responses to exogenous drivers such as regional climate change, pathogenic attacks, or widespread human activity (Mottl et al, 2021). Ecologists are recognising the importance of quantifying RoC of environmental drivers such as temperature, toxins, and salinity on ecosystems (Pinek et al, 2020) and are developing new and powerful numerical tools for space–time analysis of community compositional data over time intervals of decades (e.g. Legendre and Gauthier, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The larger the sampling scale considered, the greater the likelihood of detecting environmental variation in space or time (Wiens, 1989). Consequently, environmental change is characterized not only by its mean and variance, but by the dynamics of its variance in space and time (its stochasticity , Shoemaker et al, 2019; Table 1), its rate of change (Pinek et al, 2020) and its velocity , which comprises both the spatial and temporal dimensions of environmental variation (Burrows et al, 2014). These heterogeneities affect both deterministic and stochastic processes influencing ecological populations (Shoemaker et al, 2019; Waldock et al, 2018) and thus, greater effort should be made to incorporate such heterogeneities into ecological theory and experiments.…”
Section: Population Dynamics: Environmental Variabilitymentioning
confidence: 99%